Multiregionalism and Multilateralism Asian-European Relations in a Global Context - van der Velde, Paul; Stokhof, Wim; Bersick, Sebastian (ICAS Publications Series / Edited Volumes, 2006)
The Asia-Europe Meeting (ASEM, est. 1996) is an interregional forum which consists of the members of the European Union and the Association of Southeast Asian Nations and China, Japan and South Korea. The main components of the ASEM process include political dialogue, economy, education and culture. Multiregionalism and Multilateralism focuses on the institutionalsiation of intra-regional and inter-regional cooperation in the international system with emphasis on the changing relationship between the EU, China and India. The role of ASEM in this relationship is growing more important because of the growth of multilateralism as cornerstone of the international system.